The Moderating Effects of Group Work on the Relationship Between Motivation and Cognitive Load - Costley, Jamie; Lange, Christopher (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Semi-formal learning is used to describe learning that is directed towards the goals of a formal learning institution but outside of the learning structure of a specific class. Students studying online may form semi-formal groups to increase their knowledge of the content by interacting with other learners taking the same class. This study of cyber university students (n = 2042) involved looking at the relationship between semi-formal learning groups and levels of germane load.  Furthermore, this study sought to understand what role group work plays in moderating the relationship between motivation and germane load. This study found that highly motivated students had higher levels of germane load, and that group work negatively moderated that relationship. In other words, while all students benefited from group work, students with lower levels of motivation benefited more than students with high levels of motivation. This research fills an important gap by showing the value this type of group work can have for all learners, particularly those who may otherwise struggle.